Dielectric properties of Pb(Zr1/2Ti1/2)O3-Pb(Zn1/3Nb2/3)O3ceramics under compressive stress applied perpendicular to electric field - Muangjai Unruan (2018)
Effects of compressive stress applied perpendicular to electric field on dielectric properties of (1-x)Pb(Zr1/2Ti1/2)O3-(x)Pb(Zn1/3Nb2/3)O3 (x = 0.1-0.5) ceramics were investigated. The results showed that the superimposed compression stress had pronounced effects on the dielectric properties of PZT-PZN ceramics. With increasing compressive stress the dielectric constant of the ceramics decreased, while the dielectric loss tangent increased. The observations were mainly interpreted in terms of competing influences of the domain switching through non-180°domain walls, clamping of domain walls, and de-aging mechanisms. Interestingly, the observed changes of the dielectric properties with the perpendicular compressive stress were generally similar to those under the parallel stress. Copyright © Taylor & Francis Group, LLC.